Analisis Kuantitatif Artemisinin dari Ekstrak Metanol Tanaman Artemisia Annua L. Menggunakan Densitometer - Isnawati, Ani; Gitawati, Retno (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2009)
Artemisinin is the best antimalaria for chloroquine resistant P. falciparum recommended by WHO in a combination therapy. Artemisinin is isolated from Artemisia annua L (family: Asteraceae) that can grow as it should be in Indonesia and has cult1'vated by BPTO Tawangmangu in order to self-provide for raw material antimalarial. One of the important analysis is method for measuring artemisinin concentration in extract. The method should be more rapid, accurate, and suitable with the instruments available. Measuring analysis are used to determine cultivated result and to analyze cost beneﬁt raw material malaria medicine. The method will also be validated for accuracy, precision, selectivity, sensitivity and linearity. It is found that maximum wave length of artemisinin is 366 nm with TLC-densitometiy validated method, shown a good linearity, a coeﬁcient of corelation of 0.99976, a detection limit of 0.028 mg/mL, and a quantitative limit of 0.094 mg/mL. Artemisinin concentration obtained from methanol extract is 0. 221% with a recovery concentration of 1 01,08%.